THE EFFECTIVENESS OF LEARNING USING E-MODULES BASED ON PROBLEM BASED LEARNING TOWARDS PHYSISCS STUDENT LEARNING OUTCOMES - Br Ginting, Anayosi; Bukit, Nurdin (IPER (Indonesian Physics Education Research), 2023)
This research aims to design e-module based on problem based learning in work and energy materials. This research method uses Research and Development (R&D) with ADDIE model that are Analysis, Design, Development, Implementation, Evaluation. The research population was students in SMA Negeri 1 Tanah Pinem Class X Science. The data instruments used in this research consisted of validation questionnaires for material expert, media expert, teacher, and student responses questionnaires. The effectiveness quality of the e-module is seen from the pretest and posttest results with N-gain of 0.78 in the high category which shows that the class had increase learning outcomes in the high category. Based on the data, it can be concluded that the e-modules based on problem based learning on work and energy materials are valid and effective.